Fabrication of Guided Tissue Regeneration Membrane Using Lignin-Mediated ZnO Nanoparticles in Biopolymer Matrix for Antimicrobial Activity - Bilal, Bushra; Niazi, Rimsha; Nadeem, Sohail; Farid, Muhammad Asim; Nazir, Muhammad Shahid; Akhter, Toheed; Javed, Mohsin; Mohyuddin, Ayesha; Rauf, Abdul; Ali, Zulfiqar; Naqvi, Syed Ali Raza; Muhammad, Nawshad; et al. (Frontiers in Chemistry, 2022)
Periodontal disease is a common complication, and conventional periodontal surgery can lead to severe bleeding. Different membranes have been used for periodontal treatment with limitations, such as improper biodegradation, poor mechanical property, and no effective hemostatic property. Guided tissue regeneration (GTR) membranes favoring periodontal regeneration were prepared to overcome these shortcomings. The mucilage of the chia seed was extracted and utilized to prepare the guided tissue regeneration (GTR) membrane. Lignin having anti-bacterial properties was used to synthesize lignin mediated ZnO nanoparticles (~Lignin@ZnO) followed by characterization with analytical techniques like FT-IR (Fourier-transform infrared spectroscopy), UV-Visible spectroscopy, and SEM (Scanning electron microscope). To fabricate the GTR membrane, extracted mucilage, Lignin@ZnO, and polyvinyl alcohol (PVA) were mixed in different ratios to obtain the thin film. The fabricated GTR membrane was evaluated using a dynamic fatigue analyzer for mechanical properties. Appropriate degradation rates were approved by degradability analysis in water for a different interval of time. The fabricated GTR membrane showed excellent anti-bacterial properties against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) bacterial species.